Endovascular treatment of post-traumatic carotid-cavernous fistulae with latex detachable balloons - Szkup, Piotr (Division of Radiology, 2023)
Carotid cavernous fistula (CCF) is an abnormal connection between the carotid artery and the cavernous sinus. The CCF's are usually classified in three ways: 1. Pathologically, as spontaneous or traumatic; 2. Hemodynamically, into high-flow or low-flow; or 3. Angiographically, as direct or indirect. The Barrow angiographic classification is most commonly used. It is based on the pattern of arterial supply and has therapeutic implications.